The Effects of Family Cultural Capital upon Parenting Styles: A Study among Heads of Household in Rasht - S. Pourrahimi; M. A. Kan’ani, Ph.D.; H. Hallajzadeh, Ph.D. (خانواده و پژوهش, 2020)
Nowadays, the structure of societies has an interwoven social space of various forms of capital that distinguishes social situations hierarchically. In this regard, cultural capital plays an important role as a bridge between economy and culture and causes the family, as a cultural and social variable, to have significant effects on socialization of the children. Therefore, the attitudes and behaviors of parents, which are manifested in the form of parenting styles, require careful perusal. The purpose of this study was to examine the effects of cultural capital upon parenting styles. The statistical population of the study comprised the heads of household in Rasht. In this study, 383 heads of household from five districts of Rasht were selected through random stratified sampling method. The instruments included a researcher-made questionnaire based on Bourdieu’s theory of cultural capital as well as Baumrind’s Parenting Style Questionnaire (1991). The obtained data were analyzed by Pearson correlation and multivariate regression. The overall results showed that there was a significant relationship between cultural capital and parenting styles. This relationship was negative for the authoritarian style and positive for the authoritative and permissive styles. Based on the results of multivariate regression analysis (enter method), the entire independent variables used in this study (embodied capital, objectified capital, institutionalized capital, socio-economic status) accounted for 29.3%, 43.8%, and 17.8% of the changes in dependent variables (authoritarian, authoritative, and permissive styles), respectively. In addition, institutional capital and socio-economic status had the greatest impact on parenting styles.